Tumor Microenvironment in Ovarian Cancer: Function and Therapeutic Strategy - Yang, Yanfei; Yang, Yang; Yang, Jing; Zhao, Xia; Wei, Xiawei (Frontiers in Cell and Developmental Biology, 2020)
Ovarian cancer is one of the leading causes of death in patients with gynaecological malignancy. Despite optimal cytoreductive surgery and platinum-based chemotherapy, ovarian cancer disseminates and relapses frequently, with poor prognosis. Hence, it is urgent to find new targeted therapies for ovarian cancer. Recently, the tumour microenvironment has been reported to play a vital role in the tumorigenesis of ovarian cancer, especially with discoveries from genome-, transcriptome- and proteome-wide studies; thus tumour microenvironment may present potential therapeutic target for ovarian cancer. Here, we review the interactions between the tumour microenvironment and ovarian cancer and various therapies targeting the tumour environment. Keywords: ovarian cancer, tumour microenvironment, anti-angiogenesis therapy, tumour-associated macrophage-targeted strategies, immune checkpoint inhibitors.